Morphometric Characterization of Stingless Bees in Central Lampung Regency - Maharani, Annisa Lidya; Priyambodo; Elly Lestari Rustiati; Minanti Mayda Ashari; Yuliana Andriyani; Aril Afandi; Septi Wahyu Lestari; Shifa Sandra; Natasya Thesalonika; Winarno; Muhammad Febriansyah; Dian Neli Pratiwi (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Indonesia is recognized as one of the most biodiverse countries in the world, including in its diversity of stingless bee species. Diversity analysis is essential as a key consideration in optimizing outcomes in stingless bee cultivation practices. Morphometric analysis represents one of the methods used to assess stingless bee diversity; however, its application remains limited in Lampung Province. This study involved the collection of samples from seven different colonies across two regions in Central Lampung Regency. Morphometric measurements were conducted on eight specific parameters. The resulting morphometric data were then compared to published measurements of 20 reference species. Based on these comparisons, the morphometric characteristics of the stingless bee samples from Central Lampung indicate a close resemblance to species within the genera Heterotrigona, Tetragonula, and Geniotrigona.